Building Marketing Communication Mix to Increase Consumer Loyalty Oppo Mobile Phones of Students of STIE Dharma Putra Pekanbaru - Indriaty, Indriaty; Wibowo, Yudho; Nanda Ria, Bayu Sedih (InJEBA : International Journal of Economics, Business and Accounting, 2024)
This study aims to determine the effect of marketing communication mix on the loyalty of Oppo mobile phone consumers among STIE Dharma Putra Pekanbaru students. The marketing communication mix variables consist of Advertising, Sales Promotion, Personal Selling, Public Relations, and Direct and Digital Marketing. The population in this study were STIE Dharma Putra Pekanbaru students and used a judgmental sampling technique totaling 42 respondents. The results of the study showed that the variables of advertising, Sales promotion, Personal Selling, Public Relations, and Direct and digital marketing had a partial effect on Oppo Mobile Phone Consumer Loyalty and the Marketing Communication Mix Variable had a simultaneous effect on Consumer Loyalty. The results also showed that the contribution of the marketing mix influenced Oppo Mobile Phone Consumer Loyalty by 54.8%, the rest was influenced by other variables not examined in this study.